2020
DOI: 10.18585/inabj.v12i1.945
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment and Aerobic Exercise Enhances Spatial Memory and Synaptophysin Expression in Rats

Abstract: BACKGROUND: Exposure to environmental enrichment has a positive effect on brain function, including improved cognition. Environmental enrichment has many aspects, including social interactions, object stimulations, and physical activities. Exercise and environmental enrichment can be considered to improve cognitive function with different underlying mechanisms. This study aims to compare the effects of environmental enrichment and aerobic exercise at both synaptic and whole-organism levels using synapyophysin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…These findings, support our hypothesis that physical activity and EE can synergically promote the hippocampal potential towards an increased level of cognitive efficiency. Consistent with our data, a recent study [21] reported that the combination of EE with running exercise enhanced the spatial memory in the water maze task and increased the synaptophysin levels within the hippocampus of healthy rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings, support our hypothesis that physical activity and EE can synergically promote the hippocampal potential towards an increased level of cognitive efficiency. Consistent with our data, a recent study [21] reported that the combination of EE with running exercise enhanced the spatial memory in the water maze task and increased the synaptophysin levels within the hippocampus of healthy rats.…”
Section: Discussionsupporting
confidence: 93%
“…with our data, a recent study [21] reported that the combination of EE with running exercise enhanced the spatial memory in the water maze task and increased the synaptophysin levels within the hippocampus of healthy rats.…”
Section: Discussionsupporting
confidence: 90%